Sustainable design guidelines for new and existing schools in Egypt - Harb, Sara (AUC Knowledge Fountain, 2019)
As a global society, we are faced with an ever-growing number of sustainability challenges in the social, environmental and economic sectors. Visions for addressing such challenges have been put forward in international blueprints and policy agreements on advancing sustainable development. In these documents and agreements, education has been identified as a crucial avenue for pushing forward sustainable behaviors. Education is the fundamental element for the development of any nation, and its shortage has a direct effect on the social, environmental and economic development of the country (El Baradei & Baradei, 2004). Turning schools into sustainable schools has been a research and policy focus for years, especially throughout the UN Decade of Education for Sustainable Development. Building codes and practices play an important role in turning schools into places of sustainable learning and behavior. Previous research has addressed the concept of sustainable schools extensively, in the lights of the sustainable school design criteria and the positive impacts of having sustainable physical spaces for education. However, none cater for the Egyptian context, and are simultaneously based on building assessment standards, as well as the integration of appropriate social, environmental, and economic sustainability themes. The research project explores the requirements of Egyptian schools in the implementation of sustainable school designs and architectural changes. The thesis takes a qualitative research method with an inductive approach, in which theory development is based on and evolves with the study's findings. The thesis will make suggestions for the content of a new guideline, based on the available literature as well as on the analysis of detailed data collected based on the observation of school grounds and daily school routines and procedures during a series of school visits. The directing parameters of the guideline are based on sustainable building assessment guidelines, Egypt's pressing social, economic and environmental concerns, pedagogy of educational environments, students' social, psychological, and developmental needs, in order to develop a holistic framework. The guideline is divided into two main sections; new and existing schools. The guideline is further divided into three main sustainability categories: energy, water, and habitat; which is following the same category division adopted by EGGBC in the Tarsheed guidelines. The procedures of the research use a case study approach that focuses on one public school in Cairo, Gamal Abd El-Nasser which is located in Boulaq El Dakrour (BD), one of the poorest informal areas located in the western urban area of Greater Cairo within the boundaries of Giza Governorate. Criteria for selecting the school as a case study included choosing a preparatory school where the overall school infrastructure and conditions were of medium quality standards, making the school a potential candidate for upgrading its school infrastructure and processes to become a sustainable school in the future. The developed guideline is implemented in the case study school to demonstrate the flexibility, affordability and simplicity of attaining the required credits within the guidelines. The school scores a total of 9 out of 26 points in the Energy category, 7 out of 18 points in the Water category, 3 out of 12 points in the Indoor Environmental Quality sub-category, 6 out of 6 points in the Materials sub-category, and 36 out of 41 points in Sustainable Sites sub-category. This provides a sum of 56 out of 100 points, which awards the school a silver rating.